The Influence of Information Systems and Knowledge on the Implementation Effectiveness of Livin' by Mandiri Application - Soegiastuti, Janti; Purnomo, Gunawan Setio (Faculty of Economics and Business UNTAG Semarang, 2022)
This study aimed to analyze the effect of information systems and user knowledge on the implementation effectiveness of Livin’ by Mandiri application. The research population is Bank Mandiri KCP Semarang MT Haryono customers who have used Livin’ by Mandiri as many as 466,856 customers. The number of samples used was 100 people who were taken using simple random sampling. The data collected were analyzed using multiple linear regression. The results showed that the information system and knowledge had a positive and significant effect on the implementation effectiveness of Livin’s by Mandiri application. The results of the study concluded that customer knowledge about the application system has a more dominant influence on the implementation effectiveness compared to knowledge. According to this result, service providers of Livin by Mandiri should update their information systems, provide good complaint services, and educate consumers through social media channels.